359. The PERSON project: A neuro-rehabilitative device provided as SaaS tool. (December 2018) - Monaco, A.; Bellotti, R.; Da Pelo, P.; Diacono, D.; Luongo, C.; Sforza, G.; Tangaro, S.
Abstract : Purpose: The cognitive and computational neuroscience developed new neuro-rehabilitative tools able to treat subjects suffering from the early symptoms, in order to give priority to a home environment. In this way the curative treatment does not burden on the hospital and the patient's psychological disorientation. Recent studies have shown the efficacy of using video games to improve cognitive processes caused by aging physiological effect and neurodegenerative disease avoiding drug treatment. Methods: The PERSON project proposed rehabilitative tools such as serious game connected to EEG interface (electroencephalography paradigm through Brain Computer Interface) and haptic devices. This project regards a strategic synergy between research and public health, to implement a technology based on Virtual Reality and software solutions for personalized medicine basing on the cloud infrastructure of the ReCaS data center (https://www.recas-bari.it/index.php/en/ ). Results: Within the PERSON project we have developed a completely open source and innovative system to interface the game device with computational resources. We exploited the container technology to implement a genetic algorithm to study neural responses through EEG activity. Conclusions: We provided a Software as a Service (SaaS) tool for therapeutic purposes in patients with mild cognitive impairment. This represents a method to improve the quality of life of patients by using complex and not invasive technology, freely and safely.